Breast Augmentation in Swyer Syndrome Patient - Tania, Vika; Wardhana, Aditya (Jurnal Plastik Rekonstruksi, 2012)
Background: The number of breast augmentation in Indonesia has been raised, especially in young women. Women with disorders of sex development (DSD) can be one of our patients that come for breast augmentation. These patients may also have other problems that can lead to serious disease in her later life, such as malignancies which has 30% probability.Patients and Methods: We report one case of female with 46 XY karyotype and normal female phenotype. She appeared to be normal female but did not develop secondary sexual characteristics at puberty with Tanner classi!cation M1P1, did not menstruate, and had streak gonads in ovarian localization. This gonadal dysgenesis syndrome is also called Swyer syndrome.Result: A clinical team consists of plastic surgeons, gynecologist, psychiatrist, geneticist was build to manage our patient comprehensively. We performed breast augmentation, laparoscopic gonadectomy, and psychological support.Summary: Patient with disorder of sex development (DSD) can be one of our patients who come for breast augmentation. One must pay attention to subtle sign leading to DSD patients such as, history of amenorrhea, wide chest and lack of women body curve. Complete evaluation of sexual development is needed before performing breast augmentation.